Tricksters in the Madhouse : Lakers vs. Globetrotters, 1948 - Christgau, John (University of Nebraska Press, 2004)
"In February 1948 the brand-new, all-white Minneapolis Lakers were arguably the greatest basketball team in America, favored to win the World Professional Basketball Tournament later that year. Meanwhile the Harlem Globetrotters, at the center of black basketball, were riding their own incredible 103-game winning streak. Best known to white audiences for their clowning and comedy, the Globetrotters were not even thought to be in the same league with the mighty Lakers. So when these two powerhouses met for the first time - on February 19, 1948, before an audience of eighteen thousand in Chicago Stadium - basketball fans everywhere were in for an eye-opening performance."